Effect of Fertilizers on Yield Characteristics of Mustard (Brassica juncea L. Czern & Coss) - A.Lone1,KA.Bhat2,S.M.Razvi2,S.A.Wani3, N.Wani2,S.Akhter2,S.Rashid4,N.H.Masoodi4,W.A.Payne5, M.R.Mir1*,M.Mobin1,N.A.Khan1,M.A.Bhat2,N (Journal of Phytology, 2010)
A factorial randomized field experiment was conducted on mustard (Brassica juncea L. Czern & Coss var. Alankar) at Aligarh to study the effect of different combinations of phosphorous and potassium applied as monocalcium superphosphate and muriate of potash respectively (each at the rate of 30, 60, 90 kg P2O5 and K2O ha-1) on yield and yield attributes of mustard. In addition, a uniform dose of urea at the rate of 80 kg N ha-1 was applied. At harvest, various yield characteristics including number of pods plant-1 number of seed pod-1, seed yield and oil yield were studied. The effect of phosphorus alone as well as in combination with potassium was significant. Treatments 60 kg P2O5 ha-1 and 60 kg P2O5 + 60 kg K2O ha-1 proved optimum and the increase in seed yield was due to increase in pods plant-1 and seeds pod-1. Key words: Mustard, Phosphorous, Potassium, Seed yield, Oil yield characteristics <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">M. R. Mir et al. Effect of Fertilizers on Yield Characteristics of Mustard (Brassica juncea L. Czern & Coss). J Phytol 2/10 (2010) 20-24